2010
DOI: 10.1115/1.4002396
|View full text |Cite
|
Sign up to set email alerts
|

Dropwise Condensation Underneath Chemically Textured Surfaces: Simulation and Experiments

Abstract: Experimental observations of dropwise condensation of water vapor on a chemically textured surface of glass and its detailed computer simulation are presented. Experiments are focused on the pendant mode of dropwise condensation on the underside of horizontal and inclined glass substrates. Chemical texturing of glass is achieved by silanation using octyl-decyl-tri-chloro-silane (C18H37C13Si) in a chemical vapor deposition process. The mathematical model is built in such a way that it captures all the major phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
45
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(45 citation statements)
references
References 39 publications
0
45
0
Order By: Relevance
“…65 Model simulation results were compared with the experimental data and it was found that an increase in static contact angle and tilt angle resulted in a decrease in the surface coverage of the droplets. High tilt angles resulted in a larger number of small drops and higher heat transfer coefficient.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…65 Model simulation results were compared with the experimental data and it was found that an increase in static contact angle and tilt angle resulted in a decrease in the surface coverage of the droplets. High tilt angles resulted in a larger number of small drops and higher heat transfer coefficient.…”
mentioning
confidence: 99%
“…In many experimental studies, water vapor at a specific humidity was sent onto cool surfaces resulting in rapid condensation. [49][50][51]53,58,61,62,65 On the other hand, condensation of water vapor from ambient air (without sending vapor to cool surfaces) was also studied. 59,63,64 Many studies also investigated the growth dynamics of condensed droplets applying theoretical models and simulation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In another study [38], the best configuration was when filmwise condensation was on the upper part of the flat plate and dropwise condensation was on the lower part, since film rivulets would clean the dropwise condensation surface. Since the majority of heat transfer occurs through the smallest drops in dropwise condensation [39], droplet sweeping reduces droplet size, thus increasing heat transfer [40][41][42].…”
Section: Introductionmentioning
confidence: 99%
“…It is a common phenomenon in nature and encountered in many fields, ranging from molecular clusters to rain-drop formation in clouds as well as transport process in chemical industry, environment engineering, heat transfer and energy systems (Andrieu et al 2002;Sikarwar et al 2012;Bordoloi and Longmire, 2012;Sellier and Trelluyer, 2011).…”
Section: Introductionmentioning
confidence: 99%